1996
DOI: 10.1006/viro.1996.0116
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of HIV-1 Nef: Identification of Two Mutants That Are Temperature-Sensitive for CD4 Downregulation

Abstract: The Nef protein of HIV-1 is capable of performing at least two functions: reduction of cell-surface expression of CD4, the viral receptor, and enhancement of HIV-1 infectivity. Here we report the results of assays of CD4 downregulation by nef point mutants. Areas of high charge density and highly conserved sequence motifs were targeted. In general, mutations in the carboxyl-terminal half of the protein had more deleterious effects than did those in the amino-terminal half. A single mutant nef allele was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 0 publications
9
60
0
Order By: Relevance
“…Indeed, none of the five mutants having lost PAK2 binding capability among those studied (Nef G2A , Nef P72A/P75A , Nef P69A , Nef PR105/106AA , and Nef ⌬57-66 ) induced kidney and lung diseases. But the problem with this interpretation is the evidence that some of these mutations are known to affect other functions of Nef, in addition to its binding to PAK: namely abrogating its binding to Hck through indirect structural changes for the P72A/P75A mutation (41,90,91) and disrupting CD4 down-regulation and CD3 signaling for the R105A/R106A mutation (56,81,92,93). It therefore appears that PAK2 binding to Nef may be required for induction of kidney and lung diseases in Tg mice but is clearly not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, none of the five mutants having lost PAK2 binding capability among those studied (Nef G2A , Nef P72A/P75A , Nef P69A , Nef PR105/106AA , and Nef ⌬57-66 ) induced kidney and lung diseases. But the problem with this interpretation is the evidence that some of these mutations are known to affect other functions of Nef, in addition to its binding to PAK: namely abrogating its binding to Hck through indirect structural changes for the P72A/P75A mutation (41,90,91) and disrupting CD4 down-regulation and CD3 signaling for the R105A/R106A mutation (56,81,92,93). It therefore appears that PAK2 binding to Nef may be required for induction of kidney and lung diseases in Tg mice but is clearly not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies against the Ins(1,4,5)P 3 -receptor type I Rbt04 were kindly provided by Dr. J. Parys (Leuven, Belgium). Polyclonal antibodies against the HIV-1 Nef were as described previously (50). Anti-mouse/rabbit horseradish peroxidase-conjugated IgG were purchased from Amersham Pharmacia Biotech, and anti-mouse/rabbit fluorescein-5-isothiocyanate-conjugated IgG was from DAKO (Copenhagen).…”
Section: Methodsmentioning
confidence: 99%
“…It was previously reported that residue C142 is critical for the correct folding of Nef and that a Nef mutant with C142 to A substitution is unstable (56). Fig.…”
Section: Substitution Of K144 With Arginine Abolished Nef-mediated CDmentioning
confidence: 99%